An ultrahigh 84.3% fill factor for efficient CH3NH3PbI3 P-i-N perovskite film solar cell. (February 2022) - Li, Chen; Xu, Fan; Li, Yujiao; Li, Ning; Yu, Huanqin; Yuanb, Beilei; Chen, Zhaolai; Li, Liang; Cao, Bingqiang
Highlights: High quality perovskite films are grown by spin-coating MAPbI3 crystal based precursor solution. These perovskite films are of (0 0 1) orientation with reduced structure defects and lower Urbach energy. The MAPbI3 crystal precursor based P-i-N solar cells achieves an ultrahigh 84.3% fill factor and 19.8% efficiency. Abstract: The fill factor (FF) is a key parameter of solar cell that is strongly dictated by carrier recombination and affects the photovoltaic performance. Here, we report an 84.3% FF record for CH3 NH3 PbI3 (MAPbI3 ) based perovskite solar cell (PSC) with typical P-i-N structure and high efficiency close 20%. It is well known the perovskite precursor purity can significantly influence the final polycrystalline thin film quality. Highly (1 1 0)-oriented perovskite films with aligned grains and reduced structure defects are grown by spin-coating highly-purity MAPbI3 crystal based film precursor solution. The low-defect and highly-oriented perovskite film not only enhances light-absorption ability with broaden light-response range but also improves photocarriers transportation and extraction, which results in an impressive short-circuit current density (JSC ) and the ultrahigh FF of the PSC. This perovskite crystals precursor strategy for preparing high-quality MAPbI3 film can be easily applied to other perovskite compositions for further development of industrial-scale manufacture of solar cells.